Inhibition of Nerve Growth Factor Signaling Alleviates Repeated Dural Stimulation-induced Hyperalgesia in Rats. (1st February 2019) - Zhou, Huiru; Wang, Xueying; Wang, Sha; Liu, Chaoyang; Fu, Qingqing; Qin, Guangcheng; Zhou, Jiying; Chen, Lixue
Highlights: Repeated IS dural infusions induced cutaneous hyperalgesia in rats' periorbital region and hind paw. NGF neutralization alleviated IS-induced hyperalgesia and downregulated PKC and ASIC3 in the TNC. Inhibition of NGF signaling suppressed CGRP and c-Fos expression in the TNC. Abstract: Our previous study showed that acid-sensing ion channel 3 (ASIC3) in the trigeminal nucleus caudalis (TNC) is involved in the pathogenesis of recurrent migraine. ASIC3 is regulated by nerve growth factor (NGF), which induces hyperalgesia in various pain disorders. Neutralization of NGF is considered an effective treatment method. However, the contribution of NGF to repeated migraine-like attacks in chronic migraine (CM) remains unclear. Therefore, this study investigated the effect of NGF on ASIC3 expression in the TNC and the role of NGF signaling in chemical dural stimulation-induced hyperalgesia. A rat model was established by repeated dural infusions of inflammatory soup (IS) for seven days to simulate CM attacks. After repeated IS infusions, cutaneous hyperalgesia appeared in the rats' periorbital region and hind paws, which showed significantly lower pain thresholds. IS infusions upregulated the mRNA and protein of NGF in the TNC, and NGF was mainly expressed in the cytoplasm of TNC neurons. An intracerebroventricular injection of an anti-NGF-neutralizing antibody relieved the cutaneous hyperalgesia of CM rats and decreased protein kinase C (PKC), ASIC3, calcitonin gene-related peptide (CGRP) and c-Fos expression in the TNC. Moreover, intracerebroventricular injection with the PKC blocker chelerythrine chloride alleviated IS infusion-induced hyperalgesia and reduced ASIC3, CGRP and c-Fos levels in the TNC. These results indicate that NGF might regulate ASIC3 expression via PKC activity in the TNC following repeated IS dural stimulation, and this signaling pathway might participate in IS-induced hyperalgesia.